Fetal Outcome in Premature Rupture of Membrane - A Study Done in the Tertiary Level Specialized Hospital in Bangladesh (Community Based Medical Journal, 2014)
A descriptive cross-sectional study was done in the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from February to July of 2008, on 50 pregnant women with more than 28 weeks of pregnancy both primigravid and multigravid with rupture of membranes prior to labor, to find out the effect of premature rupture of membrane on fetal outcome. 48 live births were observed and there were 2 fetal loss. Among those newborns, 28 (58.33%) were male and 20 (41.66%) were female. 54.16% of babies had APGAR score at 5 minutes after birth was >7 and those needed no treatment. APGAR score was 7 in 45.82% babies; all of them were treated and cured. Among the newborns, 52.08% babies had birth weight > 2500 gm, 45.83% had their birth weight in between 1500 and 2500 gm, while 1 (2.08%) was between 1000 and 1500 gm. However, 22 (45.83%) were affected by the consequences of PROM and birth process. Among them, 36.36% developed jaundice, 29.27% suffered from birth asphyxia, and RTI and neonatal sepsis were evident in 18.18% each. 15% babies were treated conservatively and 7% babies were treated in the neonatal ward being admitted into it. There was no neonatal loss.CBMJ 2014 January: Vol. 03 No. 01 P: 25-28